Ethical Principles for Judges - (:unkn) unknown (My University, 2016)
The publication of Ethical Principles for Judges is the latest in a series of stepsto assist judges in carrying out their onerous responsibilities. It represents aconcise yet comprehensive set of principles addressing the many difficult ethicalissues that confront judges as they work and live in their communities. It alsoprovides a sound basis to promote a more complete understanding of the roleof the judge in society and of the ethical dilemmas they so often encounter.